The Effects of the Early Retirement Age on Retirement Decisions - Dayanand Manoli; Andrea Weber (Institute for the Study of Labor (IZA), 2016)
We present quasi-experimental evidence on the effects of increasing the Early Retirement Age (ERA) on older workers' retirement decisions. The analysis is based on social security reforms in Austria in 2000 and 2004, and administrative data allows us to distinguish between pension claims and job exits. Using a Regression Kink Design, we estimate that, within a birth cohort, a 1.0 year increase in the ERA leads to a 0.4 year increase in the average job exiting age and a 0.5 year increase in the average pension claiming age. When the ERA increases, many older workers remain in their jobs longer.
Keywords: H55; J21; J22; J26; 330; retirement; early retirement age; pension reform; life cycle labor supply; regression kink design